2009
DOI: 10.4076/1757-1626-2-7197
|View full text |Cite
|
Sign up to set email alerts
|

A case of hepatocellular carcinoma with skin injury of the upper abdominal wall after transcatheter arterial chemoembolization: a case report

Abstract: IntroductionTranscatheter arterial chemoembolization has been widely used to treat advanced hepatocellular carcinoma that cannot be treated by local ablation therapies or surgical resection. The effectiveness of transcatheter arterial chemoembolization in prolonging survival has been well established, and approximately one third of newly discovered hepatocellular carcinoma patients were repeatedly treated by transcatheter arterial chemoembolization in Japan. Various kinds of complications have been reported, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 12 publications
0
17
0
2
Order By: Relevance
“…The patient was treated with oral steroids, remained clinically stable and recovered within 5 weeks [3]. Similar complications due to patent hepatic falciform arteries have also been reported to affect transcatheter arterial chemoembolization (TACE) for unresectable HCC [7][8][9]. Prophylactic embolization of a patent hepatic falciform artery has been recommended where appropriate, to prevent radiation-induced complications to the anterior abdominal wall [2].…”
Section: Discussionmentioning
confidence: 97%
“…The patient was treated with oral steroids, remained clinically stable and recovered within 5 weeks [3]. Similar complications due to patent hepatic falciform arteries have also been reported to affect transcatheter arterial chemoembolization (TACE) for unresectable HCC [7][8][9]. Prophylactic embolization of a patent hepatic falciform artery has been recommended where appropriate, to prevent radiation-induced complications to the anterior abdominal wall [2].…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have also reported complications of supraumbilical skin rash and pain associated with chemoembolization. 11 Similarly, it has been hypothesized that these side effects might be caused by the distribution of chemotherapeutic agents through the hepatic falciform artery. 11 The presence of an angiographically identifiable falciform artery varies, and is reportedly found in 25% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Supraumbilical skin rash has been reported to be a relatively rare complication compared to other complications associated with TACE 2–5 . SUSR is thought to be caused by inflow of the chemotherapeutic agent into the hepatic falciform artery (HFA), 2 which branches from the left or middle hepatic artery, runs along the hepatic falciform ligament, and connects with the peripheral branch of the internal thoracic artery or the superior epigastric artery distributed around the umbilicus 3 .…”
mentioning
confidence: 99%
“…The incidence of the HFA detected on angiography has been reported uncommonly, ranging from 2% to 24.5%, but was reported to be relatively high on postmortem anatomical dissection 6 . These differences for detection on hepatic angiography seem to be low velocity of arterial flow and similarity of the direction of the HFA with other arteries, including the hepatic artery and cystic artery which run close to the HFA 5 . Although hepatic angiography for our patient was also retrospectively evaluated, the HFA was not detected.…”
mentioning
confidence: 99%
See 1 more Smart Citation